Penguatan Ekonomi Masyarakat Melalui Pemilahan Sampah: Model Manajemen Berbasis Komunitas di Tangerang Selatan - Yandi Asmana; Cinta Rahmi; Farhat Abas; Aditya Purnomo; Iftihal; Safina (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study aims to empower the Cipayung Subdistrict community through strengthening the community-based waste management system (TPS3R) to enhance economic productivity and environmental sustainability. A participatory approach involving observations, community meetings, focus group discussions, and capacity-building programs in waste processing, management, and digital marketing was applied. The intervention improved institutional capacity, technical skills, organizational management, and community participation despite initial challenges. Although conducted in a single TPS3R unit, the study demonstrates that institutional strengthening and continuous capacity development can effectively support sustainable waste management. It offers a practical, replicable empowerment model for policymakers, practitioners, NGOs, and researchers promoting sustainable urban development.